Co-morbidity of alcohol and psychiatric problems: impaired moral-ethical self as sources of irrational beliefs among custodial patients (2013)
Alcohol and drug problems are pervasive throughout the world and constitute major disruptive conditions to people's social and family lives. This study examined the comorbidity of substance use and psychiatric problems among patients in a psychiatric setting. The central hypotheses in this study are that substance abuse impairs one's moral-ethical self which in turn leads to a cicious circle of behaviours, especially the generation of irrational beliefs: Confirming the hypothesis that the emergence of a psychiatric condition through alcohol and drugs is a product of irrational thoughts and beliefs, the study established a significant negative correlation between moral-ethical self and irrational beliefs (r = -335; P <.05). It was also confirmed through Analysis of Variance (ANOVA) that there is a significant main effect of impaired moral-ethical self on generation of irrational beliefs. (F{1,42) = 6.10; <.05), Main effect of unimpaired moral-ethical self was not significant. Also, a t-test for independent samples show a statistically significant difference between high moral-ethical patients and low moral-ethical patients (t = -,199, df (44), p<.05). Participants with low moral-ethical self relapse more into bouts of irrational beliefs than a comparative group. The results were discussed in relation to past findings and health policy to reduce substance related psychiatric problems among people